Auditory performance and speech intelligibility among children with cochlear implant under a state-sponsored insurance scheme: a cross-sectional study - Selvavinayagam, T. S.; Subramaniam, Sudharshini; Kumar P., Senthil (International Journal Of Community Medicine And Public Health, 2021)
Background: Cochlear implant is the intervention for improving the auditory performance and speech ability for children between 6-12 years with congenital deafness under the Chief Minister’s Comprehensive Health Insurance Scheme, a state-sponsored insurance scheme in Tamil Nadu. Until 2020, 4107 children had been provided with a cochlear implant under the scheme. However, the outcome of this intervention was not studied so far. Hence, as a program evaluation auditory performance and speech intelligibility among patients who received cochlear implant under the scheme is studied. Methods: A cross-sectional study was conducted among 203 patients who had received a cochlear implant at least 1 year ago. Children were evaluated for auditory performance and speech intelligibility using revised Categories of Auditory Performance (CAP) and Speech Intelligibility Rating (SIR) scores by trained speech therapists in Government Medical College hospitals. The proportion of good scorers in CAP (level ≥7) and SIR (category ≥ 3) was computed. The difference in proportion between different demographics was tested using the Chi-square test and Fischer exact test. Results: The median CAP and SIR scores of the children were 8 (Interquartile Range – 4) and 3 (IQR – 2) respectively. Almost 2/3rd of the children had good auditory performance and speech intelligibility. Factors that were associated with good auditory performance and speech intelligibility were being a girl child, getting the implant before 3 years of age, and getting it in a private institution. Conclusions: Gender and age at implant influences auditory performance and speech intelligibility after cochlear implant. Hence, early screening for deafness should be made a routine to enable early detection and management, thereby preventing permanent disability.